2021
DOI: 10.1177/0886260521993924
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment and Subjective Well-being in Chinese Emerging Adults: A Process Model Involving Self-esteem and Self-compassion

Abstract: Child maltreatment is negatively associated with subjective well-being in emerging adulthood, but the understanding of the mechanisms of this relationship is incomplete. Guided by the stress process model incorporated with a life-course perspective, the present study examined the protective roles of self-related resources (self-esteem and self-compassion) in this association, while considering various maltreatment types (physical abuse, physical neglect, emotional abuse, emotional neglect, and sexual abuse). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…Nevertheless, the majority of current studies regarding child maltreatment were conducted in developed countries, and more research efforts from developing countries are needed [ 29 ]. The most recent estimates of child abuse and neglect exposure among Chinese youth ranged from 20% to 47% [ 30 , 31 ], which was comparable to other nations’ estimates [ 32 ]. It is critical to research the lived experiences of Chinese youth who have been maltreated, as well as the long-term effects of maltreatment on their adult well-being.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Nevertheless, the majority of current studies regarding child maltreatment were conducted in developed countries, and more research efforts from developing countries are needed [ 29 ]. The most recent estimates of child abuse and neglect exposure among Chinese youth ranged from 20% to 47% [ 30 , 31 ], which was comparable to other nations’ estimates [ 32 ]. It is critical to research the lived experiences of Chinese youth who have been maltreated, as well as the long-term effects of maltreatment on their adult well-being.…”
Section: Introductionmentioning
confidence: 53%
“…The current study also hypothesized that (3) participants who were maltreated during childhood would exhibit lower levels of DoS, hope, positive coping strategies, and life satisfaction, as well as higher levels of negative coping strategies; and (4) the mediating effects would be different between participants who were maltreated during childhood and their counterparts who were never maltreated. Given the consistent findings in the literature regarding the relationship between self-esteem and childhood psychological maltreatment, as well as subjective well-being among Chinese emerging adults [ 32 , 33 ], in the current study, we included self-esteem as a control variable.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, physical and emotional maltreatment were negatively associated with later life satisfaction, social support, and resilience, which is consistent with previous studies [ 55 , 56 , 57 ]. Individuals who have experienced childhood maltreatment, including physical and emotional maltreatment, may have biased internal working models of interpersonal relationships [ 58 ], which may contribute to low levels of resilience and social support. Similarly, childhood maltreatment, as one adverse childhood experience, may have negative effects on individuals’ attributions [ 59 ], which may lead to low levels of life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Turner et al (2017) revealed a connection between polyvictimisation and lower levels of self-esteem, suggesting that individuals who experience victimisation in differing or repeated forms will reflect appraisals of others that they are unworthy or disliked, which becomes a key message in their self-regard. Self-blame, low perceived personal control and a low working model of self due to trauma experiences were identified in individuals who had experienced multiple forms of childhood trauma (Turner et al, 2017;Wu et al, 2021). Some research into the impact of trauma on identity formation refers to possible selves and who the person could have been if not for their experience of childhood trauma.…”
Section: Identity Trauma and Self-constructionmentioning
confidence: 99%